Economic and social progress in Latin America : 1986 report - Inter-American Development Bank (IADB) (Washington, D.C. : Inter-American Development Bank, 1986)
The Inter-American Development Bank (IDB) has documented very important and useful analytical data on contemporary economic and social progress in Latin America and the Caribbean, covering the entire decades of the 1980s. This volume is the 1986 edition which is focused on the changing structure of the agricultural sector in Latin America being presented as part II
Includes bibliographical footnotes.
lje 08/10/2018
Ref
Keywords: Economic development; Economic growth; Agricultural development; Latin America